Limo - Jenkins, Dan (Book collections on Project MUSE., 2013)
Decades before it saturated the airwaves, Dan Jenkins and Bud Shrake actually invented reality TV--and skewered it into a comic novel that was way ahead of its time. Frank Mallory is a big gun at one of the four major networks. Cruising around Manhattan in his ""Silver Goblet,"" a Rolls Royce limo, he finds that life in the fast lane is beginning to unravel. Having to deal with the departure of his wife, his boss ""The Big Guy,"" and crazed Hollywood stars--while at the same time having to maintain a high-stakes job--all tend to make Frank Mallory, well, act out. After Frank struggles to fill.